2017
DOI: 10.14716/ijtech.v8i8.731
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Carbon Material Obtained from Coconut Coir Dust by Hydrothermal and Pyrolytic Processes

Abstract: Since 2004, graphene has risen in popularity owing to its superior properties. However, limits to the scale of production methods have rendered graphene a costly material. Moreover, existing production methods require chemicals that are detrimental to the environment. This study uses Coconut Coir Dust (CCD) as a carbon precursor and an intermediate product in the manufacturing of graphene. Firstly, CCD sieved into a 100 mesh was carbonized using a hydrothermal method at temperatures of 235 o C, 250 o C, and 26… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…The fragments endings act as defects producing an increase the D band intensity. These results are in agreement with a previous report [45].…”
Section: Raman Characterizationsupporting
confidence: 94%
“…The fragments endings act as defects producing an increase the D band intensity. These results are in agreement with a previous report [45].…”
Section: Raman Characterizationsupporting
confidence: 94%
“…The energy yield tended to decrease along with the increasing temperature. potential for electrochemical applications of hydrochar has even grown [37][38][39][40][41].…”
Section: Hydrochar and Its Potential Applicationsmentioning
confidence: 99%
“…Several studies showed that hydrochar is applicable as a source of solid fuel, for soil amendment, as nutrients for plant growth, and as a material to absorb soil and water pollutants 31, 33–36. The potential for electrochemical applications of hydrochar has even grown 37–41.…”
Section: State‐of‐the‐art Reviewmentioning
confidence: 99%
“…Graphene, which is generally a monoatomic two-dimensional sheet-like material with sp2-hybridized carbon atoms arranged in a hexagonal or honeycomb-like structure, and its thickness identical to an atom diameter, is one example of these materials with documented pro-osteogenic effects (Hermenean et al, 2016;Kusrini et al, 2019). However, it possesses a challenge to produce the materials (Supriadi et al, 2017). Another example is mesoporous silica nanoparticles (MSN).…”
Section: Introductionmentioning
confidence: 99%